2020
DOI: 10.3390/jcm9061639
|View full text |Cite
|
Sign up to set email alerts
|

Current Challenges in Chronic Bronchial Infection in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Currently, chronic obstructive pulmonary disease (COPD) patients and their physicians face a number of significant clinical challenges, one of which is the high degree of uncertainty related to chronic bronchial infection (CBI). By reviewing the current literature, several challenges can be identified, which should be considered as goals for research. One of these is to establish the bases for identifying the biological and clinical implications of the presence of potentially pathogenic microorganisms in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 111 publications
0
25
0
6
Order By: Relevance
“…Microorganisms are frequently observed in the airways of COPD patients, both in stable state and during exacerbations. The isolation of potentially pathogenic microorganisms (PPM) such as Hemophilus influenzae , Streptococcus pneumoniae , or Pseudomonas aeruginosa from respiratory samples does not fit the definition of colonization, since it is associated with tissue damage and an inflammatory response [ 24 , 25 ]. Recently, a clinical feature of chronic bronchial infection (CBI) has been suggested to be the appearance of the same PPM in at least three sputum cultures in a year, each separated by at least a month [ 26 ].…”
Section: Bronchiectasismentioning
confidence: 99%
See 3 more Smart Citations
“…Microorganisms are frequently observed in the airways of COPD patients, both in stable state and during exacerbations. The isolation of potentially pathogenic microorganisms (PPM) such as Hemophilus influenzae , Streptococcus pneumoniae , or Pseudomonas aeruginosa from respiratory samples does not fit the definition of colonization, since it is associated with tissue damage and an inflammatory response [ 24 , 25 ]. Recently, a clinical feature of chronic bronchial infection (CBI) has been suggested to be the appearance of the same PPM in at least three sputum cultures in a year, each separated by at least a month [ 26 ].…”
Section: Bronchiectasismentioning
confidence: 99%
“…It is well recognized that there is a strong association between CBI and COPD exacerbations. Most patients with CBI and frequent bacterial exacerbations produce colored/purulent sputum even in the stable state, have more severe dyspnea and an impaired quality of life, and may fulfill radiological criteria for bronchiectasis in chest CTs [ 24 , 25 , 26 , 27 ]. Interestingly, a recent prospective study reported that the presence of chronic purulent sputum, number of PPM isolations, and hospitalizations due to the exacerbation of COPD are independent risk factors of bronchiectasis progression in patients with moderate-to-severe COPD [ 28 ].…”
Section: Bronchiectasismentioning
confidence: 99%
See 2 more Smart Citations
“…51 Colonization implies no harm to the host, and, by definition, it would not require any type of treatment, but PPMs in stable COPD are associated with increased inflammation, increased frequency and severity of exacerbations and faster decline in pulmonary function; therefore, the term colonization is no longer considered adequate. 52 Regarding the treatment of chronic bronchial infection in chronic airway diseases, there is limited experience in asthma and COPD. The isolation of Pseudomonas aeruginosa has been shown to be associated to a greater risk of exacerbation in asthma, and the AMAZES study evidenced that azithromycin at a dose of 500 mg 3 times a week, as a treatment added to the usual medication, is capable of reducing severe exacerbations and improving the quality of life of poorly controlled asthmatics despite a combination of ICS/LABA.…”
Section: Therapeutic Goalsmentioning
confidence: 99%